2019
DOI: 10.1039/c9nr01069f
|View full text |Cite
|
Sign up to set email alerts
|

Deviations from Vegard's law and evolution of the electrocatalytic activity and stability of Pt-based nanoalloys inside fuel cells byin operandoX-ray spectroscopy and total scattering

Abstract: Deviations from Vegard's law inherent for nanoalloy catalysts can explain their behavior under operating conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 78 publications
5
45
0
Order By: Relevance
“…The higher Pt concentration in these alloys is most likely the reason for that, but it should be noticed that this law is seldom perfectly obeyed, as discussed in Refs. [47,48]. The evaluation of the L1 0 order parameter for the FePt reference layer revealed a high degree of ordering with a value of 0.93, which is close to the theoretical maximum S max of 1 [Fig.…”
Section: Structural Properties and Microstructuresupporting
confidence: 70%
“…The higher Pt concentration in these alloys is most likely the reason for that, but it should be noticed that this law is seldom perfectly obeyed, as discussed in Refs. [47,48]. The evaluation of the L1 0 order parameter for the FePt reference layer revealed a high degree of ordering with a value of 0.93, which is close to the theoretical maximum S max of 1 [Fig.…”
Section: Structural Properties and Microstructuresupporting
confidence: 70%
“…In this study, 0.25 wt%, 0.5 wt%, 1.0 wt%, and 5.0 wt% supported PtNiCo–PtNiOCoO catalysts were prepared and tested. Characterizations of the PtNiCo–PtNiOCoO nanoparticles with different compositions by HE-XRD indicated that these nanoparticles are the fcc-type structure characteristic of a solid solution 34 , 35 .…”
Section: Methodsmentioning
confidence: 99%
“…We recognise that the peak B energy shift with electrodeposition time were not strictly linear (Fig. 6) and deviations from Vegard's law are often observed [58]. Nonetheless, we found that it still provides useful approximations as an alternative method for quantifying the amounts of the varying Cu species in the films.…”
Section: X-ray Absorption Spectroscopymentioning
confidence: 83%